INCREASING PKN LEARNING OUTCOMES AND COMMUNICATION ABILITY THROUGH JIGSAW COOPERATIVE LEARNING MODE AT CLASS V SDN LEBAK GEDE, PULOMERAK DISTRICT, CILEGON CITY - Siti Futirot (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2021)
ABSTRACTCivic education learning (PKN) in schools is essential for developing the nation's character. However, its implementation in schools, especially at SDN Lebak Gede, still does not show effective learning. The purpose of this study was to see the results of applying the jigsaw cooperative learning model on PKN learning outcomes and communication skills. The research method uses School Action Research. Therefore, the object of this research is the teacher and students of class V. The data collection instrument uses an assessment scale, observation sheets, and questionnaires. The results showed that teacher activity and student communication skills were in the excellent category in the first cycle, and student learning outcomes were still low. In comparison, the results of the second cycle, teacher activities, communication skills, and student learning outcomes are good. Therefore, the jigsaw cooperative learning model can improve PKN learning outcomes and communication skills.Keywords: Cooperative, Jigsaw, PKN Learning Outcome, Communication Skills.